BENTUK DAN MAKNA SIMBOLIK TARI SEBLANG DI DESA OLEHSARI KABUPATEN BANYUWANGI JAWA TIMUR - Hadi Subagyo (Greget, 2000)
This (is] Study Article [is] more focused (by) (at) Seblang dance in countryside ritual ceremony [in] Olehsari district (ofJ executed Amaryllis Banyuwangi sub-pmvince one year once. This dance function as symbolic communications [among/bet ween] perpetrat or with audience, perpet rator with perpetrator, and also audience with audience, so that in show activity or this Seblang ceremony happened a social interaction, and even become symbolic communications (among/between] society with its ancestor, so that give meaning which enough komplek in lifeÂ Keyword: Seblang, ritual.